The Impact of the Frequency of Credit Ratings Changes on Stock Return Volatility: Evidence from the S&P 500 - Yan,Ying; Nguyen,Anh Thu (2025)
This study investigates the relationship between the frequency of credit ratings changes and stock return volatility using a dataset of publicly listed U.S. firms with annual credit ratings from the past ten years to construct both cross-sectional and panel datasets across different time windows. The main empirical approach of this thesis is fixed effects panel regression with clustered estimator, and results consistently show a positive and statistically significant association between the frequency of credit ratings changes and stock return volatility. Through using categorical variables, directional subsamples to validate the findings, we find the key driver in credit ratings changes’ impact on volatility is rating downgrades. This study contributes to the literature by highlighting the long-term implications of credit ratings activity and points to future research opportunities in the area of information persistence.
Keywords: credit rating; volatility; frequency